Comparison of surgical complication between immediate implant and autologous breast reconstruction after mastectomy: A multicenter study of 426 cases. Issue 6 (27th September 2018) - Xu, Feng; Sun, Haihui; Zhang, Chao; Jiang, Hongchuan; Guan, Shan; Wang, Xiang; Wen, Bing; Li, Jinfeng; Li, Xiru; Geng, Cuizhi; Yin, Jian
Abstract : Background and Objectives: There is a lack of multicenter immediate breast reconstruction data comparing the surgical complication of implant and autologous breast reconstruction, especially in China. In this study, we used the data from eight centers to study the complications and their risk factors in this population. Methods: Sociodemographic and clinicopathological data were obtained and compared for patients who received immediate implant and autologous breast reconstruction after breast cancer surgery in the eight hospitals between 2012 and 2016. Logistic regression analysis was used to identify risk factors associated with the complication of breast reconstruction. Results: Immediate autologous reconstruction (IAR) was associated with significantly higher rates of overall complications ( P  = 0.036), fat liquefaction ( P  < 0.001), and reconstructive failure ( P  = 0.019), but lower rates of wound complications ( P  = 0.01) compared with the immediate implant reconstruction (IIR) at the median follow‐up time of 13.6 months. With the logistic regression analysis, older patient (odds ratio [OR], 2.22; 95% confidence interval [CI], 1.15‐4.28; P  = 0.017), and obesity (OR, 2.17; 95% CI, 1.08‐4.37; P  = 0.030) were significant predictors of increased complications. Conclusion: Our multicenter results demonstrated that the rates of overall complications and reconstruction failure were higher after IAR than IIR. These findings can be used to better help surgeons and their patients with objective and reliable information to assist in selecting the modality of reconstruction.